Spatial evolution characteristics of ion and electron flow for 300 W class low-power Hall thruster - Xinwei Chen (AIP Publishing LLC, 2021)
The Faraday probe and cylindrical Langmuir probe were used to characterize the downstream ion and electron spatial evolution of a 300 W class low-power Hall thruster. The time-averaged ion current density, electron energy probability function, plasma potential, electron temperature, and electron density measurements were conducted at discharge voltages of 200–400 V and anode mass flow rates of 0.65 and 0.95 mg s−1 in the range of 100–500 mm axially and −100 to 100 mm radially downstream of the thruster. The results show that the ion and electron flows exhibit a bipolar diffusion characteristic along the radial direction. Meanwhile, the radial diffusion rate of ions in the plume is greater than the axial diffusion rate. The plasma potential decreases from 18 V at 100 mm axially from the thruster exit to 4 V at 500 mm axially and 100 mm radially. Correspondingly, the electron temperature decreases from 4.2 to 1.0 eV. The electron number density decreases from 2.6 × 1016 to 4 × 1014 m−3. A variable exponential relationship between electron temperature and electron density was observed from the measurements of electron energy probability distribution functions, with an adiabatic factor γ ranging between 1.3 and 1.4 (below the adiabatic value of 5/3). The adiabatic factor γ is considered to correlate with the anode mass flux and the spatial location of plasma, which suggests a possible dependence on the collision rate. These data are of great importance for plume model validation, improvement, plume effect evaluation, and protection mechanisms.